The Role of Financial Literacy and Risk Tolerance on Investment Decisions - Hidayatullah; Usman, Ahmadi; Utami, Dian Gita; Firmansya, Aedil; Sadiq, Muhammad (Journal of Business Administration (JBA), 2025)
This study investigates the influence of financial literacy and risk tolerance on investment decisions among students of the Business Administration and Accounting Departments at Politeknik Negeri Ujung Pandang. The importance of this research lies in the increasing awareness among students regarding the value of investing, yet their decisions often rely solely on existing financial knowledge without adequate consideration of risk management, leading to inconsistent results. Addressing this gap, the study aims to determine whether financial literacy and risk tolerance significantly contribute to students’ investment decision-making. The research employs a quantitative approach using a purposive sampling technique to select 86 respondents who have prior investment experience. Data were collected through questionnaires and analyzed using SPSS version 25, incorporating validity tests, reliability tests, normality tests, multicollinearity tests, t-tests, and F-tests. The findings revealed that financial literacy and risk tolerance simultaneously exert a positive and significant effect on investment decisions. Furthermore, both variables individually demonstrate a positive and significant influence. These results highlight that investment decisions are shaped not only by knowledge but also by the ability to manage risks, suggesting that enhancing both aspects is crucial for improving investment outcomes among students.